A study of relative humidity fiber-optic sensors - Batumalay, M. (Institute of Electrical and Electronics Engineers (IEEE), 2015)
A humidity sensor made of tapered plastic optical fiber (POF) coated with agarose gel or hydroxyethylcellulose/polyvinylidenefluoride (HEC/PVDF) detects humidity from the change in the refractive index (RI) of its coating. The RI of the deposited agarose gel or HEC/PVDF coating changes when it swells after absorbing water molecules from the surrounding. Similarly, when a tapered POF seeded with ZnO nanostructure is exposed to ambient humidity, a rapid surface adsorption of water molecules into the ZnO surface occurs. Therefore, the effective RI of its coating, which consists of the thin ZnO nanostrtucture and air, changes with humidity variation. For all of these sensors, the change in the RI of the coating affects the ability of the fiber to modulate light, thereby altering the output light intensity. In this paper, the performances of the three coating materials used with tapered fibers to construct humidity sensors are investigated. The results of the experiments show that agarose gel, HEC/PVDF, and ZnO-based optical fiber sensors are both sensitive and efficient for humidity sensing.